Promoting Transformative Learning Through Independent-Study Campus (MBKM) in Higher Institutions During the COVID-19 Pandemic - Harnida Wahyuni Adda; Pricylia Chintya Dewi Buntuang; Heni Ardianto (AL-ISHLAH: Jurnal Pendidikan, 2022)
The Independent-Study Campus (MBKM) policy in higher institutions has presented significant changes in the education paradigm during the COVID-19 pandemic. In response to the pandemic situation, the implementation of the MBKM program is initially based on online activities. This program does not present a colorful education atmosphere and focuses on student-centered learning, as well as makes the institution more autonomous with innovative learning culture which emphasizes creativity. The implementation of this program supports the student’s independence in the learning process in the higher education institutions and is flexible with the various outdoor learning which encourages personality changes and cultural exchange students. Transformative learning can be developed as an individual empowerment model that has a healthier social relationship, are more productive, are able to solve problems, make better decisions, perform self-management, optimally achieve goals, and act wisely and accountably